Safer road users: Investigating the influence of PRIME road markings on motorcycle rider behaviour. (November 2022) - Stedmon, Alex; McKenzie, David; Langham, Martin; McKechnie, Kevin; Perry, Richard; Wilson, Stuart
Highlights: Unique road trials of PRIME road markings involving 9, 594 motorcyclists. PRIME road markings produced statistically significant behavioural changes in speed, lateral lane position and braking. Identifies important factors to support improved rider behaviour and the wider 'Safe System' approach to motorcycle casualty reduction. Abstract: Innovative road markings for motorcyclists, designed as Perceptual Rider Information for Maximising Expertise and Enjoyment (PRIMEs) were installed on the approach to demanding left-hand bends at six trial sites and a comparison site across the West Highlands of Scotland. These road markings were presented as a series of 'gateways' to encourage safer riding. Video data were collected to measure motorcycle speed, lateral position, braking and use of the road markings, before and after the PRIMEs were installed. A total of 9, 594 motorcyclists were observed. Across the six trial sites, statistically significant reductions in speed were observed (at three sites). Significant changes in lateral position were observed at the final PRIME gateway marking (at one site), and at the apex of the bend (at three sites). Reduced braking was observed at three sites and there was a statistically significant increase in the use of PRIME road markings across four of the sites. No statistically significant effects were observed at the comparison site. These findings are discussed in relation to sustained effects and aspects of the 'Safe System' approach that are relevant to reducing motorcycle casualties.